ROH KUDUS AKAN MEMBERITAKAN KEPADA GEREJA-NYA HAL-HAL YANG AKAN DATANG BERDASARKAN INJIL YOHANES 16:13C - Djohan Rusli; Kuilam Bakau (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
This study aims to explain that the Holy Spirit will tell His church about things to come based on John 16:13c. It uses a descriptive qualitative method and carries out a theological approach by exploring the truth through literature review with the Bible as the main source and reliable literature. From this research, it is known that the Holy Spirit will tell His church things to come, namely the Holy Spirit is the Spirit of prophecy, the Spirit will speak about apostasy in later times, redemption is coming, the return of Christ and all the events associated with that coming and eternity. The results of this research are expected to contribute to God's church to live led by the Holy Spirit and experience spiritual maturity and grow towards Christ as the Head of the Church.